Vancomycin-Associated Leukocytoclastic Vasculitis - Makhawadee Pongruangporn; David J. Ritchie; Dongsi Lu; Jonas Marschall (Case Reports in Infectious Diseases)
Vancomycin is U.S. Food and Drug Administration (FDA) approved for treatment of serious infections caused by methicillin-resistant Staphylococcus aureus (MRSA) or in individuals who have failed, cannot tolerate, or are allergic to other antibiotics. Very few cases of vancomycin-associated leukocytoclastic vasculitis have been published. We report on a patient who developed pruritus and palpable purpura in both lower extremities after receiving six days of intravenous vancomycin. Skin biopsy revealed leukocytoclastic vasculitis.